How do we measure up? A comparison of lifestyle-related health risk factors among sampled employees in South African and UK companies. (March 2018) - Milner, Karen; da Silva, Roseanne; Patel, Deepak; Salau, Sulaiman
The need to address the growing prevalence of non-communicable diseases through changing the lifestyle behaviours that contribute to them has become a global priority. Settings-based health promotion strategies such as workplace health promotion programmes are growing in an attempt to start meeting this need. In order for settings-based health promotion programmes to be successful, they need to be based on the specific risk profiles of the population for whom they are designed. Workplace health promotion programmes are becoming popular in South Africa, but there are currently few data available about the health risks and lifestyle behaviours of the South African employed population. In order to obtain such data and reward workplace health promotion initiatives, Discovery Health initiated healthy company campaigns in South Africa and the UK. These campaigns took the form of a competition to assess the healthiest companies in each country. Through these campaigns, an extensive data set was collected encompassing UK and South African employees' lifestyle behaviours and health risks. In this article, we used these data to compare self-reported physical activity levels, self-reported fruit and vegetable consumption, calculated BMI, self-reported smoking, mental health indicators, and health screening status of the UK and South African employee samples. We found significant differences across all measures, with the exception of self-reported fruit and vegetable consumption. The findings emphasise the importance of using local data to tailor workplace health promotion programmes for the population for which the programmes have been designed.